A Review On Thermal Evaporation Method To Synthesis Zinc Oxide As Photocatalytic Material - Najiha Hamid; Muhammad Zamir Othman; Syahida Suhaimi; Wan Zakiah Wan Ismail (Trans Tech Publications, 2024)
Indexed by WOS